Types of Hidden Defect (’illah) and its Presentation by Imām al Ḥākim : An Anayltical Study - Hatamleh, Thamer Abdelmohdi (Journal of Islamic and Religious Studies, 2020)
It has been rumored that “Imām al Ḥākim” was lenient in his books other than Al-Mustadrak, but he was the first-ever scholar who devised the definition of the science of ‘Ilal al Ḥadith (hidden defects of Ḥadith) and its types. Later on, Ibn Ḥajar and al Suyūṭī added comments on these types without any expansion in it. The article attempts to show Al Ḥākim's critical personality and his place in the science of ‘Ilal, through these aberrations, graduating and restricting them to scholars, and explaining how to present it scientifically through the first type as a model. It presents the theory of Al Ḥākim about the meaning of ‘Ilal al Ḥadīth and methods of knowing Al ‘Illah with a comparison to the theories of Al Balqīnī, Al Suyūṭī, and others. The article concludes that al Ḥākim mentioned the seven ways to reveal the hidden defects of the hadith.